(2х+3)² – (х–5)² = 0
(2х)² – 12х + 3² – (х² – 10х + 5²) = 0
4х² – 12х + 9 – (х² – 10х + 25) = 0
4х² – 12х + 9 – х² + 10х – 25 = 0
3х² – 2х – 16 = 0
D = 2² – 4 * 3 * (–16) = 4 + 192 = 196
√D = √196 = 14
x1 = (2 – 14) / 6 = –12 / 6 = – 2
x2 = (2 + 14) / 6 = 16/6 = 8/3 = 2 2/3
Ответ: –2; 2 2/3
5 7/12 + 1 7/8 = 5 14/24 + 1 21/24 = 6 35/24 = 7 11/24
(x-3 9/13)+5 10/13=12 4/13
x-3 9/13=12 4/13-5 10/13
x-3 9/13=6 7/13
x=6 7/13+3 9/13
x=9 16/13
x=10 3/13
3) 5/9 / 4 1/6 = 5/9 / 11/6 = 10/33
4) 6/5 * 3 1/3 = 6/5 *10/6 = 2
5) 4 1/2 *(8 6/7) *6 = 9/2 * 62/7 * 6 = 1674/7 =239 1/7
6) 5 5/7 *5/12 *5 1/4 *6/7 / 1 1/2 = 40/7 * 5/12 *21/4 *6/7 / 3/2 = 50/7
1)
10-х=5
x=10-5
x=5
Ответ 5
2)
5х*2=10
5х=10:2
5х=5
х=5:5
х=1
Ответ 1